2014
DOI: 10.1371/journal.pone.0112602
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Subunit Vaccine Immunity with Adjuvant Combinations and Delivery Routes Using the Middle East Respiratory Coronavirus (MERS-CoV) Receptor-Binding Domain as an Antigen

Abstract: The development of an effective vaccine is critical for prevention of a Middle East respiratory syndrome coronavirus (MERS-CoV) pandemic. Some studies have indicated the receptor-binding domain (RBD) protein of MERS-CoV spike (S) is a good candidate antigen for a MERS-CoV subunit vaccine. However, highly purified proteins are typically not inherently immunogenic. We hypothesised that humoral and cell-mediated immunity would be improved with a modification of the vaccination regimen. Therefore, the immunogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 35 publications
(45 reference statements)
2
105
1
2
Order By: Relevance
“…Other studies showed similar findings of antigenic property of a rRBD protein of MERS-CoV spike (S) [78,[81][82][83]. Moreover, three adjuvants-alum, IFA, CpG and poly (I:C)-in rRBD subunit vaccines were effective in producing RBD-specific cellular and humoral immune responses [84]. Since the N-terminus RBD of (S) glycoprotein is conserved in currently circulating MERS-CoV strains, this terminus is considered a possible vaccine candidate [85].…”
Section: Currently Available Antiviral Agents and Vaccinessupporting
confidence: 55%
“…Other studies showed similar findings of antigenic property of a rRBD protein of MERS-CoV spike (S) [78,[81][82][83]. Moreover, three adjuvants-alum, IFA, CpG and poly (I:C)-in rRBD subunit vaccines were effective in producing RBD-specific cellular and humoral immune responses [84]. Since the N-terminus RBD of (S) glycoprotein is conserved in currently circulating MERS-CoV strains, this terminus is considered a possible vaccine candidate [85].…”
Section: Currently Available Antiviral Agents and Vaccinessupporting
confidence: 55%
“…Further, passive immunotherapy using convalescent phase human plasma is being considered in MERS patients after its success in animal models . However, studies also demonstrate that MERS-CoV S protein-derived vaccines induce specific CD8 þ T-cell and virus-neutralizing antibodies, which could contribute to complete protection against MERS-CoV in animal models (Lan et al, 2014;Volz et al, 2015). Based on the investigations of immune memory against SARS-CoV in follow-up studies of recovered patients (discussed above), T-cell responses can provide robust long-term memory and possess a considerable potential for cross-reactivity with heterotypic coronaviruses.…”
Section: Perspectivementioning
confidence: 99%
“…Soon after the identification of MERS‐CoV, several groups developed vaccines for preclinical testing. Recombinant receptor‐binding domain (rRBD), residues 367 to 606 of MERS‐CoV spike (S) protein, has been expressed and tested in mice as a vaccine . It induced RBD‐specific immunoglobulin G (IgG) antibody when it was tested with various adjuvants such as alum, CpG, P(I:C), or IFA.…”
Section: Current Mers‐cov Vaccine Candidates Under Developmentmentioning
confidence: 99%
“…It induced RBD‐specific immunoglobulin G (IgG) antibody when it was tested with various adjuvants such as alum, CpG, P(I:C), or IFA. However, only RBD with alum or with alum and CpG was able to induce nAb . This vaccine was then taken further and tested in Rhesus macaques at 2 different dosages, in 3 homologous vaccinations regimen, with 8‐ and 17‐week intervals.…”
Section: Current Mers‐cov Vaccine Candidates Under Developmentmentioning
confidence: 99%